Successful outcome of severe COVID-19 in pregnancy: individualised approach. Issue 1 (17th January 2022) - Dave, Anupama; Joshi, Priyansha; Jaiswal, Sunil; Kapdeo, Pradnya
Abstract : A 32-year-old homemaker, 28 weeks pregnant, was admitted to a dedicated COVID-19 hospital with a history of dyspnoea for 1 day; oral and nasopharyngeal swabs were positive for SARS-CoV-2 on real-time PCR. She had type 1 respiratory failure and oxygen saturation of 88%, so was put on non-invasive ventilation. Treatment as per guidelines was started. Given her deteriorating condition, a decision to deliver was taken and induction of labour was done. Her condition improved after delivery; but on day 5, she was suspected to have rhino-orbital mucormycosis and antifungals were started. Her condition improved gradually and she was discharged home. This case highlights the importance of individualised decision-making in cases with COVID-19 infection in pregnancy and that prompt treatment of the complications like mucormycosis would be lifesaving.